(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In the second part of my text about the famous intellectual woman Katarina Bogdanović (1885– 1969), I analyze her diary notes and other archive materials showing that she was constantly in search of her true self and the limits of her freedom, engaged in an incessant examination of the existing state of society and social relations, all the while opposing the hierarchical and unquestioningly proclaimed authority: the patriarchy, educational establishments, political institutions, and the institution of the church and marriage. As a critical observer of the world and her role in it since her early youth, Katarina Bogdanović actively participated in cultural and social life, but simultaneously she was also creating a parallel world, thus using the mission and privilege given to philosophers and writers to anticipate or predict particular social phenomena and influence youth education, the formation of youth worldview, and the development of political culture in their environments.